Association between Patient Characteristics and HbA1c Levels in Type 2 Diabetes Mellitus - Nur Nunu Prihantini; Sharon Keinaa Ampang; Tiroy Sari B. Simanjuntak; Patar Hutagalung (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Type 2 Diabetes Mellitus (T2DM)  is a growing health challenge, with the International Diabetes Federation (IDF) Diabetes Atlas 2021–2023 reporting rising prevalence worldwide, including in Indonesia. Glycemic control in T2DM is commonly assessed using HbA1c levels, which reflect average blood glucose levels over the preceding 2–3 months and serve as a key indicator of treatment effectiveness. This study investigated the association between demographic characteristics (age, gender, and occupation) and HbA1c levels among patients with T2DM at Port Medical Center Hospital from 2021 to 2023. Using a cross-sectional design, secondary data were collected from the medical records of 75 eligible patients. All records meeting the inclusion criteria were analyzed. Age, gender, and occupation were treated as independent variables, while  HbA1c level was the dependent variable. Associations were tested using  Chi-square or Fisher’s Exact Test, with significance set at p < 0.05. Results showed no significant association between gender and  HbA1c (p = 0.851; OR = 0.96, 95% CI: 0.34-2.70). However, older age was strongly linked to poor glycemic control (p = 0.010; OR = 11.0, 95% CI: 1.27–95.4), and certain occupations were associated with elevated HbA1c levels (p = 0.024; OR = 9.21, 95% CI: 1.71–49.6). These findings suggest that age-related metabolic changes and occupational factors such as physical inactivity and work-related stress may contribute to inadequate glycemic control. In conclusion, age and occupation were significantly associated with HbA1c levels, while gender was not. Targeted interventions focusing on older adults and individuals with sedentary occupations are recommended, including lifestyle modification, patient education, and routine HbA1c monitoring to improve glycemic outcomes.Keywords: Type 2 Diabetes Mellitus, HbA1c, Level Age, Occupation.